Pyrite oxidation mechanism in aqueous medium. Issue 4 (31st January 2019) - Feng, Jiling; Tian, Hua; Huang, Yaling; Ding, Zhiying; Yin, Zhoulan
Abstract : The mineral pyrite is considered the most common form of the sulfide minerals. Its oxidation is a very important process in nature, which involves in the redox recycling of iron. However, because of the growing need for the industrial production, sulfide oxidation produces more and more acid mine (or rock) drainage. This acid drainage has become a heavy economic and environmental problem. This review describes the oxidation mechanism of pyrite in an aqueous medium, including general oxidation and microbial oxidation, where sulfate, ferrous ion, S 0, polysulfides, iron[III], and some intermediate species are formed. Also included is recent evidence on the electrochemical oxidation determined using the electrochemical method, X‐ray photoelectron spectroscopy (XPS), Raman spectroscopy, Fourier transform infrared spectroscopy (FTIR), and other techniques. In addition, the factors that influence the oxidation and dissolution rate, and the descriptive approaches for different species are discussed. Abstract : Oxidation mechanism of pyrite. SO3 2− and S2 O3 2− would be formed in the presence of oxygen. There are two ways of pyrite oxidation in the presence of microorganisms. One is the thiosulfate pathway; the other one is the polysulfide pathway.